Chikungunya Virus (CHIKV): The Novel Challenge to the Healthcare System - Pireh; Iffat Jamal; Syed Zulfiqar Ali Shah; Muqadas Fatima; Farheen Qadeer; Mushahid Ali (Pakistan Journal of Medical & Health Sciences, 2024)
Chikungunya (CHIKV) is a viral illness transmitted by mosquitoes, characterized by fever and intense arthralgia. It is induced by a ribonucleic acid (RNA) virus classified within the alphavirus genus of the Togaviridae family1. The word “chikungunya” originates from a phrase in the Kimakonde phrases of southern the Republic of Tanzania, indicating “to become contorted,” which characterizes the stooped posture of those experiencing pain in the joints (arthralgia)2. Two separate spread phases have been painstakingly recorded: enzootic and urban. In Africa, an enzootic lifecycle takes place in forest environment wherein arboreal bugs, mostly Aedes spp., act as vectors. Evidence implies that nonhuman primates operate as the primary stores and amplifiers during the enzootic stage, as indicated by their increased seroprevalence rates, reported incidences of viral illnesses in natural habitats, and viremia levels following experimental transmission4. It may set in motion a protracted urban transmission cycle that is totally reliant on Aedesalbopictus or Aegypti and amplifying hosts that are humans. Due in large part to the proximity of these vectors to human populations, this epidemic/endemic cycle increases the frequency with which humans come into contact with mosquito spread